The Impact of Parental Support, School Environment, Self-Efficacy, and Effort Expectancy on Innovative Work Behavior with Generative AI among SMK Students in Jambi Province - Saudagar, Ferdiaz; Musyaiyadah, Musyaiyadah; Lestari, Agus; Wijaya, Hansein Arif; Hendra, Robi (Indonesian Educational Administration and Leadership Journal (IDEAL), 2025)
his study aims to examine the influence of parental support, work environment, self-efficacy, and business expectations on the innovative work behavior (IWB) of students at the University of Jambi. Using a quantitative approach, data was collected through a structured questionnaire that was distributed to 310 students from various faculties. The research instrument has passed the validity and reliability test through Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). Structural Equation Modeling (SEM) is used to test hypotheses. The model feasibility index showed a good fit (χ²/df = 2.91; RMSEA = 0.063; CFI = 0.934; TLI = 0.921). The results showed that the work environment and self-efficacy had a significant positive influence on IWB, while parental support and business expectations did not show a significant direct influence. However, parental support has a positive effect on self-efficacy, and the work environment significantly affects business expectations, which suggests an important indirect pathway. This model explains 48.6% of the variance in IWB. The novelty of this study lies in the integration between environmental factors and personal psychological factors in a single model to predict student innovation behavior in the context of higher education. These findings provide insights for educational institutions to strengthen the potential for student innovation through improved learning environments and confidence-building programs. This research contributes to the development of science in the field of physics education by offering a model of student behavior that supports the formation of innovative, confident, and proactive learners of important attributes in the advancement of science and education. Keywords: Parental Support, Work Environment, Self-Efficacy, Effort Expectancy, Innovative Work Behavior